(untitled) (Al-Mansour Journal, 2023)
The study aimed to clarify the link and influence between customer relationship management and the quality of municipal service within a theoretical and practical framework that was conducted in the municipality of Dora. Through the pilot study, it was noted that the municipality contains an administrative structure specialized in managing customer relations in the form of a specialized department, as well as divisions that are not linked to divisions, but they require an increase in the development of their human resources specialized in providing services to citizens because of their impact on the quality of municipal service. Thus, a number of research questions were developed about the existence of a clear perception for workers in various technical and administrative disciplines regarding strategies for managing customer relations, the quality of municipal service, and the relationship and influence between them. The hypotheses were formulated within a hypothetical model in order to verify the correlation and effect between the explanatory variable (customer relationship management) and the interactive variable (service quality) in the study model. The study sample consisted of (194) working individuals (technical and administrative) in the municipality. After analyzing the data using the statistical program (SPSS V.24), the study concluded a number of conclusions that indicated the existence of a significant correlation between the study variables based on it. The results also showed a significant effect of customer relationship management on the quality of municipality service. Based on the results, the study recommended a number of recommendations.